Graphite alloy composite roller

By using modified alloy coating material and plasma spraying technology on the composite roller, the modified alloy layer is formed, which solves the problem of wear resistance and poor impact toughness performance of composite rollers under acid corrosion conditions, and significantly improves the acid corrosion stability and performance.

CN116334520BActive Publication Date: 2025-01-10HUBEI TENGSHENG TECH LLC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310145050.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-21
Publication Date
2025-01-10
Estimated Expiration
2043-02-21

AI Technical Summary

Technical Problem

The existing composite rollers have poor wear resistance and impact toughness under acid corrosion conditions, making it difficult to coordinate the performance requirements of the roller body and core materials.

Method used

The modified alloy coating material includes graphite, iron, nickel, manganese, chromium and aluminum borate whisker modified materials, combined with plasma spraying technology, a modified alloy layer is formed to enhance the wear resistance of the roller body. Toughness and acid-corrosion stability.

Benefits of technology

The wear resistance and impact toughness of the composite roller under acid corrosion conditions is significantly improved, and the acid corrosion stability is enhanced, ensuring the long-term use performance of the roller body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_6
    Figure SMS_6
  • Figure SMS_7
    Figure SMS_7
Patent Text Reader

Abstract

The invention discloses a graphite alloy composite roller, the composite roller comprises a roller base layer, a modified alloy coating material is arranged on the outer side of the roller base layer to form a modified alloy layer, and the modified alloy coating material comprises the following raw materials by weight: 2-5 parts of graphite, 65-70 parts of iron, 1-4 parts of nickel, 1-3 parts of manganese, 1-3 parts of chromium, 3-6 parts of aluminum borate whisker modifier, and 90-100 parts of treatment regulating liquid. The composite roller of the invention is formed into a modified alloy layer by plasma spraying the base layer with the modified alloy coating material, the structure of the product has excellent wear resistance and impact toughness under acid corrosion conditions, the aluminum borate whiskers are distributed in the base, the toughness and wear resistance of the product base are enhanced, and the optimized aluminum borate whisker modifier can significantly enhance the acid corrosion stability of the product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite rollers, in particular to a graphite alloy composite roller. Background Art

[0002] The outer layer and core (including the roll neck) of the roll body are made of different materials, and the two materials are metallurgically bonded. The composite roll can not only meet the requirements of the rolling mill for the wear resistance and thermal fatigue resistance of the roll body, but also ensure the toughness of the core and roll neck. The materials of the outer layer and the core are mainly selected according to the specific requirements of the frame where the roll is located for its performance. Commonly used composite roll outer layer materials include chilled cast iron, unbounded chilled cast iron, ductile iron, high chromium cast iron, alloy steel, semi-steel, high chromium steel, high-speed steel, cemented carbide, etc.; the commonly used core materials are gray cast iron, ductile iron, cast steel, and forged steel.

[0003] The composite roller is composed of a roller base layer and an alloy coating. The existing alloy coating has poor acid corrosion resistance. Under acid corrosion conditions, the wear resistance and impact toughness of the product are reduced. In order to coordinate and improve the performance of the two under acid corrosion conditions, the present invention further explores and processes it. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a graphite alloy composite roller to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] The present invention provides a graphite alloy composite roller, the composite roller comprises a roller base layer, a modified alloy coating material is arranged on the outer side of the roller base layer to form a modified alloy layer, and the modified alloy coating material comprises the following raw materials in parts by weight:

[0007] 2-5 parts of graphite, 65-70 parts of iron, 1-4 parts of nickel, 1-3 parts of manganese, 1-3 parts of chromium, 3-6 parts of aluminum borate whisker modifier, and 90-100 parts of treatment adjustment liquid.

[0008] Preferably, the modified alloy coating material comprises the following raw materials in parts by weight:

[0009] 3.5 parts of graphite, 67.5 parts of iron, 2.5 parts of nickel, 2 parts of manganese, 2 parts of chromium, 4.5 parts of modified aluminum borate whisker, and 95 parts of treatment conditioning liquid.

[0010] Preferably, the modification method of the aluminum borate whisker modifier is:

[0011] S01: Weigh 1-4 parts of stearic acid, 2-5 parts of sodium carboxymethyl cellulose, 10-20 parts of deionized water, and 1-3 parts of sodium lauryl sulfate, and prepare a ball mill;

[0012] S02: The aluminum borate whiskers are first fed into a ball mill for ball milling, and a ball milling agent of 5-10% of the total amount of the aluminum borate whiskers is added for ball milling. After the ball milling is completed, the aluminum borate whiskers are washed with water and dried;

[0013] S03: Add silicon carbide to 3-5 times the modified composite agent for stirring and compounding, with a stirring speed of 500-1000r / min and a stirring time of 30-40min. After the stirring is completed, a silicon carbide regulating liquid is obtained;

[0014] S04: Add the product of S02 into the silicon carbide conditioning liquid at a weight ratio of 1:5 and stir thoroughly, then wash with water and dry to obtain an aluminum borate whisker modification.

[0015] Preferably, the ball milling speed is 1550-1650 r / min, and the ball milling time is 30-40 min.

[0016] Preferably, the preparation method of the modified composite agent is:

[0017] 3-5 parts of lanthanum sulfate are added to 10-15 parts of chitosan aqueous solution, and then 1-3 parts of sodium alkyl sulfonate and 0.2-0.4 parts of hydrochloric acid are added, and stirred evenly to obtain a modified composite agent.

[0018] Preferably, the mass fraction of the chitosan aqueous solution is 10-20%.

[0019] Preferably, the preparation method of the treatment conditioning solution is:

[0020] S101: adding sodium alginate to deionized water at a weight ratio of 2:13 to prepare a sodium alginate aqueous solution, adding 2-5 parts of lanthanum chloride solution to 10-20 parts of the sodium alginate aqueous solution and stirring evenly;

[0021] S102: 1-3 parts of titanate coupling agent and 0.2-0.5 parts of phosphate buffer solution are stirred evenly, and then added to the product of S101, and the mixture is mixed thoroughly to obtain a treatment adjustment solution.

[0022] Preferably, the mass fraction of the lanthanum chloride solution is 10-15%; and the pH value of the phosphate buffer solution is 4.5-5.0.

[0023] Preferably, the preparation method of the composite roller is:

[0024] Step 1: Mix graphite, iron, nickel, manganese and chromium according to weight parts, and then send them into a smelting machine for complete smelting;

[0025] Step 2: Then heat the aluminum borate whisker modification to 310-350°C for 10-20 minutes, add it into step 1, stir evenly, and then cool it to set;

[0026] Step 3: Place the cooled and shaped product in step 2 in a treatment regulating liquid for infiltration treatment, with an infiltration pressure of 5-10MPa, an infiltration temperature of 40-45°C, and an infiltration time of 10-20min;

[0027] Step 4: Finally, the product of step 3 is heat treated at 400-450°C for 5-10 minutes, then cooled to room temperature at a rate of 1-3°C / min, and finally ball-milled to 100 mesh to obtain a modified alloy coating material;

[0028] Step 5: The modified alloy coating material is sprayed onto the roller base layer by plasma spraying technology to obtain the graphite alloy composite roller of the present invention.

[0029] Preferably, the plasma spraying current is 350-400A, the spraying voltage is 75-100V, the spraying distance is 90-100mm, and the powder feeding rate is 35-40g·min .

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] The composite roller of the invention is formed into a modified alloy layer by plasma spraying a modified alloy coating material on a base layer. The structure of the product has excellent wear resistance and impact toughness under acid corrosion conditions. The melt formed by graphite, iron, nickel, manganese and chromium is combined with an aluminum borate whisker modifier for optimization and modification. The aluminum borate whisker modifier is optimized by ball milling with an aluminum borate whisker and then treating with a silicon carbide regulating liquid. The aluminum borate whiskers are distributed in the base, thereby enhancing the toughness and wear resistance of the base of the product. At the same time, the optimized aluminum borate whisker modifier can significantly enhance the acid corrosion resistance of the product. In order to improve the corrosion stability, the cooled and shaped product is placed in a treatment conditioning liquid for immersion treatment. The treatment conditioning liquid is a lanthanum chloride solution combined with a sodium alginate aqueous solution to enhance the dispersibility of the lanthanum chloride solution in the treatment conditioning liquid. The lanthanum chloride solution has rare earth interface properties and enhances the interface compatibility between the raw materials. The titanate coupling agent and phosphate buffer solution are used to further optimize the interface effect of the product. Therefore, the product of step three is modified with the treatment conditioning liquid during the uniform heat treatment, and the wear resistance, toughness and acid corrosion stability of the product are further improved. DETAILED DESCRIPTION

[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0033] The graphite alloy composite roller of this embodiment comprises a roller base layer, and a modified alloy coating material is provided on the outer side of the roller base layer to form a modified alloy layer. The modified alloy coating material comprises the following raw materials in parts by weight:

[0034] 2-5 parts of graphite, 65-70 parts of iron, 1-4 parts of nickel, 1-3 parts of manganese, 1-3 parts of chromium, 3-6 parts of aluminum borate whisker modifier, and 90-100 parts of treatment adjustment liquid.

[0035] The modified alloy coating material of this embodiment includes the following raw materials in parts by weight:

[0036] 3.5 parts of graphite, 67.5 parts of iron, 2.5 parts of nickel, 2 parts of manganese, 2 parts of chromium, 4.5 parts of modified aluminum borate whisker, and 95 parts of treatment conditioning liquid.

[0037] The modification method of the aluminum borate whisker modifier of this embodiment is:

[0038] S01: Weigh 1-4 parts of stearic acid, 2-5 parts of sodium carboxymethyl cellulose, 10-20 parts of deionized water, and 1-3 parts of sodium lauryl sulfate, and prepare a ball mill;

[0039] S02: The aluminum borate whiskers are first fed into a ball mill for ball milling, and a ball milling agent of 5-10% of the total amount of the aluminum borate whiskers is added for ball milling. After the ball milling is completed, the aluminum borate whiskers are washed with water and dried;

[0040] S03: Add silicon carbide to 3-5 times the modified composite agent for stirring and compounding, with a stirring speed of 500-1000r / min and a stirring time of 30-40min. After the stirring is completed, a silicon carbide regulating liquid is obtained;

[0041] S04: Add the product of S02 into the silicon carbide conditioning liquid at a weight ratio of 1:5 and stir thoroughly, then wash with water and dry to obtain an aluminum borate whisker modification.

[0042] The ball milling speed of this embodiment is 1550-1650r / min, and the ball milling time is 30-40min.

[0043] The preparation method of the modified composite agent of this embodiment is:

[0044] 3-5 parts of lanthanum sulfate are added to 10-15 parts of chitosan aqueous solution, and then 1-3 parts of sodium alkyl sulfonate and 0.2-0.4 parts of hydrochloric acid are added, and stirred evenly to obtain a modified composite agent.

[0045] The mass fraction of the chitosan aqueous solution in this embodiment is 10-20%.

[0046] The preparation method of the treatment conditioning solution of this embodiment is:

[0047] S101: adding sodium alginate to deionized water at a weight ratio of 2:13 to prepare a sodium alginate aqueous solution, adding 2-5 parts of lanthanum chloride solution to 10-20 parts of the sodium alginate aqueous solution and stirring evenly;

[0048] S102: 1-3 parts of titanate coupling agent and 0.2-0.5 parts of phosphate buffer solution are stirred evenly, and then added to the product of S101, and the mixture is mixed thoroughly to obtain a treatment adjustment solution.

[0049] The mass fraction of the lanthanum chloride solution of this embodiment is 10-15%; the pH value of the phosphate buffer solution is 4.5-5.0.

[0050] The preparation method of the composite roller of this embodiment is:

[0051] Step 1: Mix graphite, iron, nickel, manganese and chromium according to weight parts, and then send them into a smelting machine for complete smelting;

[0052] Step 2: Then heat the aluminum borate whisker modification to 310-350°C for 10-20 minutes, add it into step 1, stir evenly, and then cool it to set;

[0053] Step 3: Place the cooled and shaped product in step 2 in a treatment regulating liquid for infiltration treatment, with an infiltration pressure of 5-10MPa, an infiltration temperature of 40-45°C, and an infiltration time of 10-20min;

[0054] Step 4: Finally, the product of step 3 is heat treated at 400-450°C for 5-10 minutes, then cooled to room temperature at a rate of 1-3°C / min, and finally ball-milled to 100 mesh to obtain a modified alloy coating material;

[0055] Step 5: The modified alloy coating material is sprayed onto the roller base layer by plasma spraying technology to obtain the graphite alloy composite roller of the present invention.

[0056] The plasma spraying current of this embodiment is 350-400A, the spraying voltage is 75-100V, the spraying distance is 90-100mm, and the powder feeding rate is 35-40g·min .

[0057] Example 1

[0058] The graphite alloy composite roller of this embodiment comprises a roller base layer, and a modified alloy coating material is provided on the outer side of the roller base layer to form a modified alloy layer. The modified alloy coating material comprises the following raw materials in parts by weight:

[0059] 2 parts of graphite, 65 parts of iron, 1 part of nickel, 1 part of manganese, 1 part of chromium, 3 parts of aluminum borate whisker modification, and 90 parts of treatment adjustment liquid.

[0060] The modification method of the aluminum borate whisker modifier of this embodiment is:

[0061] S01: Weigh 1 part of stearic acid, 2 parts of sodium carboxymethyl cellulose, 10 parts of deionized water, and 1 part of sodium dodecyl sulfate, and mix them to make a ball mill;

[0062] S02: The aluminum borate whiskers are first fed into a ball mill for ball milling, and a ball milling agent of 5-10% of the total amount of the aluminum borate whiskers is added for ball milling. After the ball milling is completed, the aluminum borate whiskers are washed with water and dried;

[0063] S03: Add silicon carbide to 3 times the modified composite agent for stirring and compounding, with a stirring speed of 500 r / min and a stirring time of 30 min. After the stirring is completed, a silicon carbide regulating liquid is obtained;

[0064] S04: Add the product of S02 into the silicon carbide conditioning liquid at a weight ratio of 1:5 and stir thoroughly, then wash with water and dry to obtain an aluminum borate whisker modification.

[0065] The ball milling speed in this embodiment is 1550 r / min, and the ball milling time is 30 min.

[0066] The preparation method of the modified composite agent of this embodiment is:

[0067] 3 parts of lanthanum sulfate are added to 10 parts of chitosan aqueous solution, and then 1 part of sodium alkyl sulfonate and 0.2 parts of hydrochloric acid are added, and stirred evenly to obtain a modified composite agent.

[0068] The mass fraction of the chitosan aqueous solution in this embodiment is 10%.

[0069] The preparation method of the treatment conditioning solution of this embodiment is:

[0070] S101: adding sodium alginate to deionized water at a weight ratio of 2:13 to prepare a sodium alginate aqueous solution, adding 2 parts of lanthanum chloride solution to 10 parts of the sodium alginate aqueous solution and stirring evenly;

[0071] S102: Mix 1 part of titanate coupling agent and 0.2 parts of phosphate buffer solution, stir evenly, add to the product of S101, continue to mix thoroughly, and obtain a treatment adjustment solution.

[0072] The mass fraction of the lanthanum chloride solution of this embodiment is 10%; the pH value of the phosphate buffer solution is 4.5.

[0073] The preparation method of the composite roller of this embodiment is:

[0074] Step 1: Mix graphite, iron, nickel, manganese and chromium according to weight parts, and then send them into a smelting machine for complete smelting;

[0075] Step 2: Then heat the aluminum borate whisker modification to 310°C for 10 minutes, add it into step 1, stir evenly, and then cool it to set;

[0076] Step 3: Place the cooled and shaped product in step 2 in a treatment regulating liquid for infiltration treatment, with an infiltration pressure of 5 MPa, an infiltration temperature of 40°C, and an infiltration time of 10 min;

[0077] Step 4: Finally, the product of step 3 was heat treated at 400°C for 5 minutes, then cooled to room temperature at a rate of 1°C / min, and finally ball-milled to 100 mesh to obtain a modified alloy coating material;

[0078] Step 5: The modified alloy coating material is sprayed onto the roller base layer by plasma spraying technology to obtain the graphite alloy composite roller of the present invention.

[0079] The plasma spraying current of this embodiment is 350A, the spraying voltage is 75V, the spraying distance is 90mm, and the powder feeding rate is 35g·min .

[0080] Example 2

[0081] The graphite alloy composite roller of this embodiment comprises a roller base layer, and a modified alloy coating material is provided on the outer side of the roller base layer to form a modified alloy layer. The modified alloy coating material comprises the following raw materials in parts by weight:

[0082] 5 parts of graphite, 70 parts of iron, 4 parts of nickel, 3 parts of manganese, 3 parts of chromium, 6 parts of modified aluminum borate whisker, and 100 parts of treatment conditioning liquid.

[0083] The modification method of the aluminum borate whisker modifier of this embodiment is:

[0084] S01: Weigh 4 parts of stearic acid, 5 parts of sodium carboxymethyl cellulose, 20 parts of deionized water, and 3 parts of sodium lauryl sulfate, and mix them to make a ball mill;

[0085] S02: The aluminum borate whiskers are first fed into a ball mill for ball milling, and a ball milling agent of 5-10% of the total amount of the aluminum borate whiskers is added for ball milling. After the ball milling is completed, the aluminum borate whiskers are washed with water and dried;

[0086] S03: Add silicon carbide to 5 times the modified composite agent for stirring and compounding, with a stirring speed of 1000r / min and a stirring time of 30-40min. After the stirring is completed, a silicon carbide regulating liquid is obtained;

[0087] S04: Add the product of S02 into the silicon carbide conditioning liquid at a weight ratio of 1:5 and stir thoroughly, then wash with water and dry to obtain an aluminum borate whisker modification.

[0088] The ball milling speed in this embodiment is 1650 r / min, and the ball milling time is 40 min.

[0089] The preparation method of the modified composite agent of this embodiment is:

[0090] 5 parts of lanthanum sulfate were added to 15 parts of chitosan aqueous solution, and then 3 parts of sodium alkyl sulfonate and 0.4 parts of hydrochloric acid were added, and stirred evenly to obtain a modified composite agent.

[0091] The mass fraction of the chitosan aqueous solution in this embodiment is 20%.

[0092] The preparation method of the treatment conditioning solution of this embodiment is:

[0093] S101: adding sodium alginate to deionized water at a weight ratio of 2:13 to prepare a sodium alginate aqueous solution, adding 5 parts of lanthanum chloride solution to 20 parts of the sodium alginate aqueous solution and stirring evenly;

[0094] S102: 3 parts of titanate coupling agent and 0.5 parts of phosphate buffer solution are stirred evenly, and then added to the product of S101, and the mixture is mixed thoroughly to obtain a treatment adjustment solution.

[0095] The mass fraction of the lanthanum chloride solution of this embodiment is 15%; the pH value of the phosphate buffer solution is 5.0.

[0096] The preparation method of the composite roller of this embodiment is:

[0097] Step 1: Mix graphite, iron, nickel, manganese and chromium according to weight parts, and then send them into a smelting machine for complete smelting;

[0098] Step 2: Then heat the aluminum borate whisker modification to 350°C for 20 minutes, add it into step 1, stir evenly, and then cool it to set;

[0099] Step 3: Place the cooled and shaped product in step 2 in a treatment regulating liquid for infiltration treatment, with an infiltration pressure of 10 MPa, an infiltration temperature of 45°C, and an infiltration time of 20 min;

[0100] Step 4: Finally, the product of step 3 was heat treated at 450°C for 10 minutes, then cooled to room temperature at a rate of 3°C / min, and finally ball-milled to 100 mesh to obtain a modified alloy coating material;

[0101] Step 5: The modified alloy coating material is sprayed onto the roller base layer by plasma spraying technology to obtain the graphite alloy composite roller of the present invention.

[0102] The plasma spraying current of this embodiment is 400A, the spraying voltage is 100V, the spraying distance is 100mm, and the powder feeding rate is 40g·min .

[0103] Example 3

[0104] The graphite alloy composite roller of this embodiment comprises a roller base layer, and a modified alloy coating material is provided on the outer side of the roller base layer to form a modified alloy layer. The modified alloy coating material comprises the following raw materials in parts by weight:

[0105] 3.5 parts of graphite, 67.5 parts of iron, 2.5 parts of nickel, 2 parts of manganese, 2 parts of chromium, 4.5 parts of modified aluminum borate whisker, and 95 parts of treatment conditioning liquid.

[0106] The modification method of the aluminum borate whisker modifier of this embodiment is:

[0107] S01: Weigh 2.5 parts of stearic acid, 3.5 parts of sodium carboxymethyl cellulose, 15 parts of deionized water, and 2 parts of sodium lauryl sulfate, and mix them to make a ball mill;

[0108] S02: The aluminum borate whiskers are first sent to a ball mill for ball milling, and a ball milling agent of 7.5% of the total amount of the aluminum borate whiskers is added for ball milling. After the ball milling is completed, the aluminum borate whiskers are washed with water and dried;

[0109] S03: Add silicon carbide to 4 times the modified composite agent for stirring and compounding, with a stirring speed of 750 r / min and a stirring time of 35 min. After the stirring is completed, a silicon carbide regulating liquid is obtained;

[0110] S04: Add the product of S02 into the silicon carbide conditioning liquid at a weight ratio of 1:5 and stir thoroughly, then wash with water and dry to obtain an aluminum borate whisker modification.

[0111] The ball milling speed in this embodiment is 1600 r / min, and the ball milling time is 35 min.

[0112] The preparation method of the modified composite agent of this embodiment is:

[0113] 4 parts of lanthanum sulfate were added to 12.5 parts of chitosan aqueous solution, and then 2 parts of sodium alkyl sulfonate and 0.3 parts of hydrochloric acid were added, and stirred evenly to obtain a modified composite agent.

[0114] The mass fraction of the chitosan aqueous solution in this embodiment is 15%.

[0115] The preparation method of the treatment conditioning solution of this embodiment is:

[0116] S101: adding sodium alginate to deionized water at a weight ratio of 2:13 to prepare a sodium alginate aqueous solution, adding 3.5 parts of lanthanum chloride solution to 15 parts of the sodium alginate aqueous solution and stirring evenly;

[0117] S102: 2 parts of titanate coupling agent and 0.35 parts of phosphate buffer solution are stirred evenly, and then added to the product of S101, and the mixture is mixed thoroughly to obtain a treatment adjustment solution.

[0118] The mass fraction of the lanthanum chloride solution of this embodiment is 12.5%; the pH value of the phosphate buffer solution is 4.7.

[0119] The preparation method of the composite roller of this embodiment is:

[0120] Step 1: Mix graphite, iron, nickel, manganese and chromium according to weight parts, and then send them into a smelting machine for complete smelting;

[0121] Step 2: Then heat the aluminum borate whisker modification to 330°C for 15 minutes, add it into step 1, stir evenly, and then cool it to set;

[0122] Step 3: Place the cooled and shaped product in step 2 in a treatment regulating liquid for infiltration treatment, with an infiltration pressure of 7.5 MPa, an infiltration temperature of 42°C, and an infiltration time of 15 min;

[0123] Step 4: Finally, the product of step 3 was heat treated at 425°C for 7.5 min, then cooled to room temperature at a rate of 2°C / min, and finally ball-milled to 100 mesh to obtain a modified alloy coating material;

[0124] Step 5: The modified alloy coating material is sprayed onto the roller base layer by plasma spraying technology to obtain the graphite alloy composite roller of the present invention.

[0125] The plasma spraying current of this embodiment is 370A, the spraying voltage is 80V, the spraying distance is 95mm, and the powder feeding rate is 37.5g·min .

[0126] Comparative Example 1

[0127] The difference from Example 3 is that no aluminum borate whisker modifier is added.

[0128] Comparative Example 2

[0129] The difference from Example 3 is that the aluminum borate whisker modifier is replaced by aluminum borate whisker.

[0130] Comparative Example 3

[0131] The difference between Example 3 is that no ball milling agent treatment is used in the preparation of the aluminum borate whisker modifier.

[0132] Comparative Example 4

[0133] The difference of Example 3 is that stearic acid is not added in the preparation of the ball mill.

[0134] Comparative Example 5

[0135] The difference from Example 3 is that sodium dodecyl sulfate was not added in the preparation of the ball mill.

[0136] Comparative Example 6

[0137] The difference from Example 3 is that no silicon carbide conditioning liquid is added in the preparation of the aluminum borate whisker modification.

[0138] Comparative Example 7.

[0139] The difference from Example 3 is that no treatment with a treatment conditioning liquid is used.

[0140] Comparative Example 8

[0141] The difference from Example 3 is that no lanthanum chloride solution is added in the preparation of the treatment conditioning solution.

[0142] Comparative Example 9

[0143] The difference from Example 3 is that no titanate coupling agent is added in the preparation of the treatment regulating solution.

[0144] Comparative Example 10

[0145] The difference from Example 3 is that the heat treatment in step 4 is not adopted.

[0146] The products of Examples 1-3 and Comparative Examples 1-10 of the present invention were subjected to conventional performance tests and placed in a 2% by mass hydrochloric acid mist for 48 hours, and then tested for performance under acid corrosion conditions;

[0147]

[0148] It can be seen from Example 3 and Comparative Examples 1-10 that

[0149] The product of Example 3 of the present invention has excellent acid resistance stability, and the product still has excellent impact toughness and wear resistance under acid corrosion;

[0150] It can be seen from Comparative Examples 1-2 that the product does not add the aluminum borate whisker modifier, and the wear resistance and toughness of the product are significantly reduced. At the same time, the aluminum borate whisker modifier is replaced by aluminum borate whiskers, and the acid corrosion stability of the product is reduced more significantly. The direct replacement effect of aluminum borate whiskers is poor, and it cannot be replaced by direct raw materials.

[0151] It can be seen from Comparative Examples 3-6 that the performance of the products tended to deteriorate when no ball mill was used in the preparation of the aluminum borate whisker modifier and the raw material ratio of the ball mill was different. At the same time, the performance of the products changed significantly when no silicon carbide conditioning liquid was added for treatment. Therefore, the silicon carbide conditioning liquid had a significant effect on the wear resistance and acid corrosion stability of the toughness of the products. At the same time, the performance effects of the aluminum borate whisker modifiers prepared by different methods were different. Only the aluminum borate whisker modifier prepared by the method of the present invention could significantly improve the wear resistance and acid corrosion stability of the toughness of the products.

[0152] It can be seen from Comparative Examples 7-10 that the treatment with the regulating liquid also has a significant improvement effect on the acid-corrosion stability of the product. At the same time, different raw material ratios have different effects. The preparation effect using the raw material ratio of the present invention is significant, and the improvement effect of the product is most obvious when combined with the uniform heat treatment in step four.

[0153] The present invention found that the silicon carbide conditioning liquid has a significant effect on the performance of the product during the preparation of the aluminum borate whisker modifier. Based on this, the present invention further explores and processes it.

[0154] In the preparation of aluminum borate whisker modifier:

[0155] Silicon carbide is fed into 4 times the modified composite agent for stirring and compounding treatment, the stirring speed is 750r / min, the stirring time is 35min, and after the stirring is completed, a silicon carbide regulating liquid is obtained;

[0156] The S02 product is added into the silicon carbide conditioning liquid at a weight ratio of 1:5 and stirred thoroughly, then washed with water and dried to obtain an aluminum borate whisker modification.

[0157] The preparation method of the modified composite agent of this embodiment is:

[0158] 4 parts of lanthanum sulfate were added to 12.5 parts of chitosan aqueous solution, and then 2 parts of sodium alkyl sulfonate and 0.3 parts of hydrochloric acid were added, and stirred evenly to obtain a modified composite agent.

[0159] The mass fraction of the chitosan aqueous solution in this embodiment is 15%.

[0160] Experimental Example 1

[0161] The only difference from the preparation of the silicon carbide conditioning solution in Example 3 is that silicon carbide is not added.

[0162] Experimental Example 2

[0163] The only difference from the preparation of the silicon carbide regulating solution in Example 3 is that silicon nitride is used as the silicon carbide raw material.

[0164] Experimental Example 3

[0165] The only difference from the preparation of the silicon carbide regulating solution in Example 3 is that the modified composite agent is directly replaced by a 2% by mass hydrochloric acid solution.

[0166] Experimental Example 4

[0167] The only difference from the preparation of the silicon carbide conditioning solution in Example 3 is that lanthanum sulfate is not added to the modified composite agent.

[0168] Experimental Example 5

[0169] The only difference from the preparation of the silicon carbide regulating solution in Example 3 is that no sodium alkyl sulfonate is added to the modified composite agent.

[0170] Experimental Example 6

[0171] The only difference from the preparation of the silicon carbide regulating solution in Example 3 is that the chitosan aqueous solution is replaced by deionized water.

[0172]

[0173] It can be seen from Experimental Examples 1-6 that the only difference in the preparation of silicon carbide conditioning liquid is that silicon carbide is not added, and the acid corrosion resistance, wear resistance, and impact toughness change most significantly, and silicon carbide is replaced by silicon nitride, and the deterioration is more obvious. The selection and addition of silicon carbide has a significant effect on improving the performance of the product;

[0174] The performance change of the modified composite agent directly replaced by a hydrochloric acid solution with a mass fraction of 2% is more obvious than the performance of the modified composite agent without adding lanthanum sulfate and sodium alkyl sulfonate. The use of the modified composite agent also has certain influencing factors on the performance of the product. At the same time, the chitosan aqueous solution is replaced by deionized water, and the performance of the product also has a certain trend of deterioration. The modified composite agent made of chitosan aqueous solution and raw materials such as sodium alkyl sulfonate and lanthanum sulfate is used to optimize the modification of silicon carbide. The prepared silicon carbide regulating solution has specificity. Only the silicon carbide regulating solution prepared by the method of the present invention has the most obvious improvement on the performance of the product.

[0175] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0176] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A graphite alloy composite roller, the composite roller comprising a roller base layer, characterized in that: A modified alloy coating material is disposed on the outer side of the roller base layer to form a modified alloy layer. The modified alloy coating material includes the following raw materials in parts by weight: 2-5 parts of graphite, 65-70 parts of iron, 1-4 parts of nickel, 1-3 parts of manganese, 1-3 parts of chromium, 3-6 parts of aluminum borate whisker modifier, 90-100 parts of treatment conditioning liquid; The modification method of the aluminum borate whisker modifier is: S01: Weigh 1-4 parts of stearic acid, 2-5 parts of sodium carboxymethyl cellulose, 10-20 parts of deionized water, and 1-3 parts of sodium lauryl sulfate, and prepare a ball mill; S02: The aluminum borate whiskers are first fed into a ball mill for ball milling, and a ball milling agent of 5-10% of the total amount of the aluminum borate whiskers is added for ball milling. After the ball milling is completed, the aluminum borate whiskers are washed with water and dried; S03: Add silicon carbide to 3-5 times the modified composite agent for stirring and compounding, with a stirring speed of 500-1000r / min and a stirring time of 30-40min. After the stirring is completed, a silicon carbide regulating liquid is obtained; S04: adding the product of S02 into the silicon carbide conditioning liquid at a weight ratio of 1:5 and stirring sufficiently, then washing with water and drying to obtain an aluminum borate whisker modification; The preparation method of the treatment regulating solution is: S101: adding sodium alginate to deionized water at a weight ratio of 2:13 to prepare a sodium alginate aqueous solution, adding 2-5 parts of lanthanum chloride solution to 10-20 parts of the sodium alginate aqueous solution and stirring evenly; S102: 1-3 parts of titanate coupling agent and 0.2-0.5 parts of phosphate buffer solution are stirred evenly, and then added to the product of S101, and the mixture is mixed thoroughly to obtain a treatment adjustment solution.

2. The graphite alloy composite roller according to claim 1, characterized in that: The modified alloy coating material comprises the following raw materials in parts by weight: 3.5 parts of graphite, 67.5 parts of iron, 2.5 parts of nickel, 2 parts of manganese, 2 parts of chromium, 4.5 parts of modified aluminum borate whisker, and 95 parts of treatment conditioning liquid.

3. The graphite alloy composite roller according to claim 2, characterized in that: The ball milling speed is 1550-1650 r / min, and the ball milling time is 30-40 min.

4. The graphite alloy composite roller according to claim 3, characterized in that: The preparation method of the modified composite agent is: 3-5 parts of lanthanum sulfate are added to 10-15 parts of chitosan aqueous solution, and then 1-3 parts of sodium alkyl sulfonate and 0.2-0.4 parts of hydrochloric acid are added, and stirred evenly to obtain a modified composite agent.

5. The graphite alloy composite roller according to claim 4, characterized in that: The mass fraction of the chitosan aqueous solution is 10-20%.

6. The graphite alloy composite roller according to claim 5, characterized in that: The mass fraction of the lanthanum chloride solution is 10-15%; the pH value of the phosphate buffer solution is 4.5-5.

0.

7. The graphite alloy composite roller according to claim 1, characterized in that: The preparation method of the composite roller is as follows: Step 1: Mix graphite, iron, nickel, manganese and chromium according to weight parts, and then send them into a smelting machine for complete smelting; Step 2: Then heat the aluminum borate whisker modification to 310-350°C for 10-20 minutes, add it into step 1, stir evenly, and then cool it to set; Step 3: Place the cooled and shaped product in step 2 in a treatment regulating liquid for infiltration treatment, with an infiltration pressure of 5-10MPa, an infiltration temperature of 40-45°C, and an infiltration time of 10-20min; Step 4: Finally, the product of step 3 is heat treated at 400-450°C for 5-10 minutes, then cooled to room temperature at a rate of 1-3°C / min, and finally ball-milled to 100 mesh to obtain a modified alloy coating material; Step 5: The modified alloy coating material is sprayed onto the roller base layer using plasma spraying technology to obtain a graphite alloy composite roller.

8. The graphite alloy composite roller according to claim 7, characterized in that: Plasma spraying current is 350-400A, spraying voltage is 75-100V, spraying distance is 90-100mm, powder feeding rate is 35-40g·min .

Citation Information

Patent Citations

  • High-strength metal ceramic material for mold

    CN107815621A

  • Thermoplastic resin composition

    JP2001064520A